Patterns of genetic diversity in European beech (Fagus sylvatica L.) at the eastern margins of its distribution range - Ciocîrlan E; Sofletea N; Ducci F; Curtu AL (iForest - Biogeosciences and Forestry, 2017)
Populations located at the periphery of the species’ distribution range may play an important role in the context of climate change. These peripheral populations may contain specific adaptations as a result of extreme environmental conditions. The aim of this paper was to assess within population genetic diversity and among population differentiation in one of the most important forest tree species in Europe, European beech (Fagus sylvatica), at the eastern margins of its natural range. We analysed four peripheral, isolated populations and five core populations from the continuous natural range along the Carpathian Mountains using a set of microsatellite markers. Higher levels of genetic diversity as measured by allelic richness (7.34 vs. 6.50) and observed heterozygosity (0.71 vs. 0.59) were detected in core populations than in peripheral ones. Population differentiation was slightly higher among peripheral populations than among core, Carpathian populations. There was strong evidence of bottleneck effects in two out of the four peripheral, isolated populations. Both core, Carpathian populations and peripheral, lowlands populations share the same chloroplast haplotype suggesting a common geographical origin from the putative Moravian refuge area. Past long distance founding events with material from the Carpathian mountain chain might explain the occurrence of small, isolated beech populations towards the steppe in the south-east of Romania. Our genetic data may contribute to a better understanding of the evolutionary history of the remnants of beech scattered occurrences at the eastern margins of species’ distribution range.